Resilience Model of the Traditional Islamic Boarding School Education System in Shaping the Morals of Student in the Midst of Modernizing Education - Jaenullah Jaenullah; Ferdian Utama; Dedi Setiawan (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The study aims to reveal the existence of the traditional pesantren education system (salaf) in shaping the morals of students in the midst of modernizing education. Traditional Islamic boarding schools are currently till a reference for the community, even thousands of people who participate in activities held by traditional pesantren, such as recitation and istighosah. The method used in this study was a case study using a qualitative research approach. This research had the subject of the kyai, teacher, male student, and female student at the Darul Falah Islamic Boarding School, OKU, South Sumatra, Indonesia. Data collection techniques used in-depth interviews, observation, and documentation studies. This study was analyzed using Miles and Huberman’s data analysis techniques : data reduction, data presentation, and drawing conclusion and verification. This study found that the resilience of the pesantren education system in shaping the morals of students in the era of globalization had strong endurance and continuity because it has four system functions. First, the system of adaptation to the pesantren education environment is carried out with a twenty-four-hour education pattern to shape the students' morals. Second, Islamic boarding schools have educational goals to shape the personality of students who have noble characters.  Third, the integration of pesantren has integrated both the institutional system and the curriculum. Fourth, there is the maintenance of the cultural pattern (latency) of the value system in the pesantren.